Numerical Simulation of Orthogonal Machining of Gallium Nitride via Smoothed Particle Hydrodynamics - Muhammad Haseeb; Hasan Aftab Saeed; Imran Sajid S. Ghumman (NUML International Journal of Engineering and Computing)
Gallium Nitride is one of the best candidates for upcoming industrial revolution due to its superior electrical properties over silicon. In the present work, we investigate the chip formation, cutting force and effective stress in diamond machining of gallium nitride by smoothed particle hydrodynamics approach based on Mohr-Coulomb material model. The comparison of the effective stress as reported by molecular dynamics studies and that predicted by the smoothed particle hydrodynamics simulation demonstrates the effectiveness of the smoothed particle hydrodynamics model.